solve the following
![\frac{3(7x - 1)}{4} - (2x - \frac{1 - x}{2} ) = x + \frac{3}{2} \frac{3(7x - 1)}{4} - (2x - \frac{1 - x}{2} ) = x + \frac{3}{2}](https://tex.z-dn.net/?f=+%5Cfrac%7B3%287x+-+1%29%7D%7B4%7D+-+%282x+-+%5Cfrac%7B1+-+x%7D%7B2%7D+%29+%3D+x+%2B+%5Cfrac%7B3%7D%7B2%7D+)
pls....
Answers
Answered by
1
Answer:
dividing by a fraction is the same as multiplying by the reciprocal of the fraction.
In some cases of simplifying an algebraic expression, the expression will be a fraction. For example,
x2+3x
x+3
has a quadratic binomial in the numerator and a linear binomial in the denominator. We have to apply the different factorisation methods in order to factorise the numerator and the denominator before we can simplify the expression.
x2+3x
x+3
=
x(x+3)
x+3
=x(x≠−3)
If x=−3 then the denominator, x+3=0 and the fraction is undefined.
Similar questions